Multiscale model based design of an energy‐intensified novel adsorptive reactor process for the water gas shift reaction. Issue 7 (13th May 2019) - Karagöz, Seçgin; Chen, Huanhao; Cao, Mingyuan; Tsotsis, Theodore T.; Manousiouthakis, Vasilios I.
Abstract: In this work, an adsorptive reactor (AR) process is considered that can energetically intensify the water gas shift reaction (WGSR). To best understand AR process behavior, a multiscale, dynamic, process model is developed. This multiscale model enables the quantification of catalyst and adsorbent effectiveness factors within the reactor environment, obliviating the commonly employed assumption that these factors are constant. Simulations of the AR's alternating adsorption‐reaction/desorption operation, using the proposed model, illustrate rapid convergence to a long‐term periodic solution. The obtained simulation results quantify the influence of key operating conditions and design parameters (e.g., reactor temperature/pressure, W cat / F CO, W ad / F CO, F H2O / F CO ratios, and pellet size) on the AR's behavior. They also demonstrate, for pellet diameters used at the industrial scale, significant temporal and axial variation of the catalyst/adsorbent pellet effectiveness factors. Finally, the energetic intensification benefits of the proposed AR process over conventional WGSR packed‐bed reactors are quantified.